Use of Draft Flights and Monitoring Systems in Agriculture in the Fight Against Pests - Zaynidinov Hakimjon Nasiridinovich; Mallaev Oybek Usmonqulovich; Modullaev Jahongir Sobir ugli (Zien Journals, 2022)
The article provides an overview of existing monitoring systems in agriculture using advanced technologies such as small unmanned aerial vehicles (UAVs). Over the past year, agricultural reports on the level of locust damage in the southern and central zones of Central Asia, Tajikistan and Uzbekistan have been analyzed. Basic systems for monitoring the condition of plants in plants, the presence of fires, the appearance of wild animals and pests are considered. The main methods of pest control and their feasibility are discussed. An analysis of the unmanned vehicle market is presented and a forecast for its further development in the agricultural sector is developed. It was noted that the widespread use of these systems in the monitoring and protection of agricultural products in Uzbekistan from pests is important and effective.
Keywords: drones; monitoring; artificial intelligence; pests